Effect of simulated gastrointestinal digestion on antioxidant, and anti-inflammatory activities of bioactive peptides generated in sausages fermented with Staphylococcus simulans QB7 - Hongying Li; Hongbing Fan; Zihan Wang; Qiujin Zhu; Jianping Wu (Food Science and Human Wellness)
Dry-fermented sausages are a good source of bioactive peptides, whose stability against gastrointestinal (GI) digestion determines their bioaccessibility. This study focused on evaluating the effect of peptide extracts from sausages fermented with Staphylococcus simulans QB7 during in vitro simulated GI digestion, including peptide profiles and antioxidant and anti-inflammatory activities. Peptides present in sausages were degraded during digestion, with molecular weight reduced from > 12 kDa to < 1.5 kDa. Besides, the content of amino acids increased from 381.15 to 527.07 mg/g, especially tyrosine being found only after GI digestion. The anti-inflammatory activities were increased after GI digestion, however, the changes in antioxidant activities were the opposite. A total number of 255, 252 and 386 peptide sequences were identified in undigested, peptic-digested and GI-digested samples, respectively. PeptideRanker, BIOPEP-UWM and admetSAR were used to further predict the functional properties and intestinal absorption of the identified peptide sequences from GI digestion. Finally, 18 peptides were discovered to possess either antioxidant or anti-inflammatory capacities.